Differences in Diversion Mechanisms at The Investigation, Prosecution and Examination Stages in Trial - Angga Bintang Putra Pratama; Andria Luhur Prakosa (Universitas Muhammadiyah Surakarta, 2026)
Children in conflict with the law require special protection to avoid the negative impacts of the formal, repressive, and potentially stigmatizing criminal justice process. The Indonesian juvenile justice system responds to this need through a restorative justice approach, manifested in the diversion mechanism, which diverts the resolution of juvenile cases from the criminal justice process to out-of-court settlements. However, the implementation of diversion at each stage of the juvenile justice process still faces procedural differences, normative constraints, and practical obstacles that affect its effectiveness. This study aims to analyze the mechanisms for implementing diversion at the investigation, prosecution, and trial stages of the juvenile justice system. This study uses a normative juridical method with a statutory and conceptual approach and is supported by a literature review through a review of primary legal materials, secondary legal materials, and scientific journals related to diversion and restorative justice. The data obtained are analyzed qualitatively to understand the regulations, differences in mechanisms, and efforts to optimize the implementation of diversion in law enforcement practices. The novelty of this study lies in a comprehensive analysis of the differences in diversion mechanisms at each stage of the juvenile justice process. The research results show that diversion during the investigation stage has a greater chance of success than during the prosecution and trial stages because the case is still in the early stages of resolution. This success is also determined by the willingness of the parties, the role of law enforcement officials, and the support of a conducive social environment. Diversion provides a more humane solution by emphasizing the restoration of relationships between the perpetrator, victim, and the community. It also serves as a crucial instrument for realizing restorative justice and legal protection for children in a more effective and sustainable manner.